Explaining Faculty Members' Perceptions of Virtual Learning Based on Various Types of Educational Interactions During the Coronavirus Disease 2019 Outbreak: A Qualitative Content Analysis - Ensiyeh Mirzaei; Mehrangiz Alinejad; Badrsadat Daneshmand (Kerman University of Medical Sciences, 2022)
Background: Given that interaction is a vital element in virtual learning, using the professors' experiences and perceptions during the coronavirus disease 2019 (COVID-19) outbreak can provide useful information about the quality of educational interactions in virtual learning courses in order to improve virtual learning.Objectives: This study aims to explain the perceptions of faculty members of Kerman universities regarding virtual learning based on educational interactions during the COVID-19 outbreak.Methods: This study was conducted with a qualitative content analysis approach in the academic year of 2021 in Kerman University of Medical Sciences and Shahid Bahonar University of Kerman. The data collection method was semi-structured interviews with 13 professors of these universities who were included in the study using purposive sampling. Data analysis was performed using the qualitative content analysis method according to the steps introduced by Graneheim and Lundman.Results: The results of this study were presented in the form of 4 main themes: 1) Teacher-learner interactions, including the tools used, how they interact, and their barriers; 2) Learner-learner interaction, learner-content interaction, and teacher-content interaction, including the professors' actions to create and increase them; 3) Teacher-teacher interactions, including professors' instructional and research interactions and their barriers; 4) Content-content interaction, which the findings indicated that professors did not pay much attention to this type of interaction.Conclusion: Virtual learning is not limited to the COVID-19 outbreak period but can be used as a supplement to face-to-face learning, even when the universities reopen; therefore, valuable experiences of professors of virtual learning can be used to strengthen various types of educational interactions and develop virtual learning in the studied universities and other universities.